Optimizing Production in the New Generation of Apricot Cultivars: Self-incompatibility, S-RNase Allele Identification, and Incompatibility Group Assignment - Herrera, Sara; Lora, Jorge; Hormaza, José I.; Herrero, Maria; Rodrigo, Javier (Frontiers in Plant Science, 2018)
Apricot (Prunus armeniaca L.) is a species of the Rosaceae that was originated in Central Asia, from where it entered Europe through Armenia. The introduction of an increasing number of new cultivars from different breeding programs is resulting in an important renewal of plant material worldwide. Although most traditional apricot cultivars in Europe are self-compatible, the use of self-incompatible cultivars as parental genotypes for breeding purposes is resulting in the introduction of a number of new cultivars that behave as self-incompatible. As a consequence, there is an increasing need to interplant those new cultivars with cross-compatible cultivars to ensure fruit set in commercial orchards. However, the pollination requirements of many of these new cultivars are unknown. In this work, we analyze the pollination requirements of a group of 92 apricot cultivars, including traditional and newly-released cultivars from different breeding programs and countries. Self-compatibility was established by the observation of pollen tube behavior in self-pollinated flowers under the microscope. Incompatibility relationships between cultivars were established by the identification of S-alleles by PCR analysis. The self-(in)compatibility of 68 cultivars and the S-RNase genotype of 74 cultivars are reported herein for the first time. Approximately half of the cultivars (47) behaved as self-compatible and the other 45 as self-incompatible. Identification of S-alleles in self-incompatible cultivars allowed allocating them in 11 incompatibility groups, six of them reported here for the first time. The determination of pollination requirements and the incompatibility relationships between cultivars is highly valuable for the appropriate selection of apricot cultivars in commercial orchards and for the selection of parental genotypes in breeding programs. The approach described can be transferred to other woody perennial crops with similar problems.